Build a application KetKers Media Advertising Based Crowdsourcing - Wibowo, Septian Agung; Wulandari, Sri Hariani Eko; Ningsih, Norma (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
KetKers is a platform website with crowdsourcing models that engaged in kind of veterinary especially for cats with an attractive design and most complete of facilities. KetKers includes 2 segments, the advertising providers (seller) and the advertising seekers (buyer). Customers can find easily what they need about their supplies, save more time and money for adoption and cat’s care, being a place that be trusted with the certified feature. Nowadays, many people are difficult to find the trust and complete website that provide all of the needs about cats, such as adopting cats, grooming, pet day care, veterinary service, mates, producing cat kennels, and the retail seller of cat supplies. Therefore, a startup platform that based on website is appear to help the sellers met the buyers and give the best offer to customer with the most facilities inside. It called KetKers. Joining KetKers, the sellers can increase the chance of their selling of good and services from KetKers’s customer. The result of the trials have shown that this startup platform can provide the facilities (grooming, pet’s care, veterinarian, mates, retailer of cat’s need and supplies with crowdsourcing models.